The prevalence and incidence of diabetes mellitus among Sami and non-Sami inhabitants of Northern Norway - Naseribafrouei, Ali (UiT The Arctic University of Norway, 2019)
The thesis is based upon data from two cross-sectional population-based surveys, the SAMINOR 1 Survey (2003-2004) and the SAMINOR 2 Clinical Survey (2012-2014). The prevalence of pre-diabetes and diabetes mellitus among Sami and non-Sami inhabitants of the 24 municipalities from North- and Mid-Norway was estimated in the SAMINOR 1 Survey. No statistically significant difference in the prevalence of pre-diabetes or diabetes mellitus was found between Sami and non-Sami participants in this study. In the SAMINOR 2 Clinical Survey, 10 municipalities from North Norway were included. The prevalence of both pre-diabetes and type 2 diabetes mellitus was statistically significantly higher among Sami participants and abdominal obesity was the most plausible explanation for it. By following participants from the SAMINOR 1 to the SAMINOR 2 Survey, the 8-year cumulative incidence of diabetes mellitus was estimated. No statistically significant difference in the 8-year cumulative incidence of diabetes mellitus was observed between Sami and non-Sami participants.